Antioxidant and Anti-inflammatory Effect of Nrf2 Inducer Dimethyl Fumarate in Neurodegenerative Diseases - Sarah A. Scuderi; Alessio Ardizzone; Irene Paterniti; Emanuela Esposito; Michela Campolo (MDPI AG, 2020)
Neurodegenerative diseases (NDs) represents debilitating conditions characterized by degeneration of neuronal cells in specific brain areas, causing disability and death in patients. In the pathophysiology of NDs, oxidative stress, apoptosis and neuroinflammation have a key role, as demonstrated by in vivo and in vitro models. Therefore, the use of molecules with antioxidant and anti-inflammatory activities represents a possible strategy for the treatment of NDs. Many studies demonstrated the beneficial effects of fumaric acid esters (FAEs) to counteract neuroinflammation and oxidative stress. Among these molecules, dimethyl fumarate (DMF) showed a valid therapeutic approach to slow down neurodegeneration and relieve symptoms in patients with NDs. DMF is a methyl ester of fumaric acid and acts as modulator of the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway as well as nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) translocation. Therefore, this review aims to examine the potential beneficial effects of DMF to counteract oxidative stress and inflammation in patients with NDs.